Differential Roles of Endothelial Cell-Derived and Smooth Muscle Cell-Derived Fibronectin Containing Extra Domain A in Early and Late Atherosclerosis. Issue 7 (July 2020) - Doddapattar, Prakash; Dev, Rishabh; Jain, Manish; Dhanesha, Nirav; Chauhan, Anil K.
Abstract : Objective: The extracellular matrix of atherosclerotic arteries contains abundant deposits of cellular Fn-EDA (fibronectin containing extra domain A), suggesting a functional role in the pathophysiology of atherosclerosis. Fn-EDA is synthesized by several cell types, including endothelial cells (ECs) and smooth muscle cells (SMCs), which are known to contribute to different stages of atherosclerosis. Although previous studies using global Fn-EDA-deficient mice have demonstrated that Fn-EDA is proatherogenic, the cell-specific role of EC versus SMC-derived-Fn-EDA in atherosclerosis has not been investigated yet. Approach and Results: To determine the relative contribution of different pools of Fn-EDA in atherosclerosis, we generated mutant strains lacking Fn-EDA in the ECs (Fn-EDA EC-KO ) or smooth muscle cells (Fn-EDA SMC-KO ) on apolipoprotein E-deficient ( Apoe −/− ) background. The extent of atherosclerotic lesion progression was evaluated in whole aortae, and cross-sections of the aortic sinus in male and female mice fed a high-fat Western diet for either 4 weeks (early atherosclerosis) or 14 weeks (late atherosclerosis). Irrespective of sex, Fn-EDA EC-KO, but not Fn-EDA SMC-KO mice, exhibited significantly reduced early atherogenesis concomitant with decrease in inflammatory cells (neutrophil and macrophage) and VCAM-1 (vascular cell adhesion molecule-1) expression levels within the plaques. In late atherosclerosis model, irrespective of sex, Fn-EDA SMC-KO mice exhibited significantly reduced atherogenesis, but not Fn-EDA EC-KO mice, that was concomitant with decreased macrophage content within plaques. Lesional SMCs, collagen content, and plasma inflammatory cytokines (TNF-α [tumor necrosis factor-α] and IL-1β [interleukin-1β]), total cholesterol, and triglyceride levels were comparable among groups. Conclusions: EC-derived Fn-EDA contributes to early atherosclerosis, whereas SMC-derived Fn-EDA contributes to late atherosclerosis. Abstract : Supplemental Digital Content is available in the text.